Pengembangan Dan Pendampingan Aplikasi Sistem Informasi Simpan Pinjam Pada Pengurus BUMDes Desa Wongkai Satu: Development and Assistance of Savings and Loan Information System Application in the Management of Village-Owned Enterprises from Wongkai Satu Village (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
The development and assistance of savings and loan applications in the Wongkai Satu Village Bumdes(Village-Owned Enterprises) Management is an important step in strengthening microfinance services at the village level. This process aims to improve accessibility, efficiency, and transparency in the management of savings and loans in the Wongkai Satu Village community group. Application development is carried out by a comprehensive needs analysis by involving the collection of information from Bumdes administrators and community members to understand the challenges, needs, and expectations related to savings and loan services as a reference for application development planning which is carried out by formulating features that are in accordance with the needs of the application. The development and assistance of savings and loan applications aims to achieve several benefits. First, increasing the accessibility of microfinance services for rural communities, especially those in remote locations. Second, increasing efficiency and accuracy in the management of savings and loan transactions, which can help in local economic growth, increasing transparency and accountability in Bumdes operations, which can strengthen the trust of community members and other stakeholders.